Multifunctional nanocomposites between natural rubber and polyvinyl pyrrolidone modified graphene. (January 2016) - Zhang, Xumin; Wang, Jingyi; Jia, Hongbing; You, Shiyu; Xiong, Xiaogang; Ding, Lifeng; Xu, Zhaodong
Abstract: Polyvinyl pyrrolidone (PVP) modified reduced graphene oxide (PRGO) was prepared through chemical reduction of graphene oxide (GO) in the presence of PVP. The PRGO/natural rubber (NR) nanocomposites were fabricated by mixing PRGO aqueous dispersion with NR latex, followed by coagulation and vulcanization. The structure of PRGO was characterized using UV–vis absorption spectroscopy, Atomic force microscope, Solid state 13 C NMR and X-ray photoelectron spectroscopy. The thermal conductivity, swelling and mechanical properties of PRGO/NR nanocomposites were also investigated. The results showed that GO was reduced effectively in the presence of PVP, and the PVP molecules were absorbed on the basal plane of reduced graphene oxide (RGO) through non-covalent interactions. With the increase of PRGO, thermal conductivity and storage modulus of PRGO/NR nanocomposites increased, whereas solvent uptake decreased. Compared with unfilled NR, NR with 5 phr (parts per hundred rubber) PRGO had a 30% increase in thermal conductivity and 37% decrease in solvent uptake. Under the condition of adding 3 phr PRGO, the tensile and tear strength of NR nanocomposite were improved by 23% and 150%, respectively.